Assessment of severity and preventability of adverse drug reactions to chemotherapy in eastern Nepal - Shah, Rekha; Sapkota, Sulav; Sah, Lalita; Shah, Arbindra (Journal of Chitwan Medical College, 2025)
Introduction: Chemotherapy is associated with a high risk of adverse drug reactions (ADRs), which can affect treatment outcomes and patient quality of life. Limited data are available from Nepal on the severity and preventability of chemotherapy-induced ADRs. This study aimed to assess the types, severity, and preventability of ADRs in cancer patients receiving chemotherapy in a tertiary care hospital. Method: A hospital-based cross-sectional study was conducted among cancer patients receiving chemotherapy in the day care unit of the Oncology Department, Birat Medical College Teaching Hospital, over 6 months period from May 19 to Nov 20, 2024. The ADRs identification, severity, and preventability were assessed. Data were analysed in SPSS-26 using descriptive statistics, Chi-square/Fisher’s exact test, and logistic regression to identify predictors of preventable ADRs. Result: All 195 patients experienced some form of ADRs. Moderate ADRs were 98(50.3%), mild 57(29.2%) and severe 40(20.5%). Preventable ADRs were 52(26.7%), probably preventable 69(35.4%) and non-preventable 74(37.9%). Association between chemotherapy regimen and ADR was not significant (p=0.073). We did not identify independent predictors of preventable ADRs. Conclusion: Moderate ADRs were most common among cancer patients on chemotherapy. The female gender had significant associations with severity. None of the independent variables (gender, age, type of cancer, comorbidity) was significantly associated with ADR preventability. About two-thirds of ADRs were preventable, highlighting a critical need to enhance pharmacovigilance and monitoring systems.